Diagnóstico de parvovirus canino en las clínicas veterinarias de la ciudad de Huaquillas mediante la prueba de Elisa - Jiménez Pulla, María Cecilia (2012)
This research was conducted in the city of Huaquillas, province of El Oro, from 1 June until September 5, 2011. Raised the following objectives: 1. Diagnosing canine parvovirus in dogs with symptoms of gastro problems attending different veterinary clinics in the city of Huaquillas by ELISA. 2. Determine the percentage of canine parvovirus by age, sex, race and origin of the infected animals. 3. Develop an epidemiological map of canine parvovirus according to place of origin of the positive animals. We investigated a sample of 100 dogs suspected of canine parvovirus. The samples used are dog feces, which were obtained in different Veterinary Clinics in the city, taking gender, race, age and place of origin. The method for diagnosis of canine parvovirus was quick proof CPC / CCV Ag Anigo. We obtained a rate of 26% Canine Parvovirus.